Effect of Mechanical Surface Treatment on Shear Bond Strength of Orthodontic Brackets to 3D Printed and Milled CAD/CAM Provisional Materials: An In Vitro Study - Abdulaziz A. Alzaid; Khalid K. Alanazi; Lulu A. Alyahya; Maha N. Alharbi; Hatem Alqarni; Mohammed Alsaloum; Hayam A. Alfallaj; Ghada S. Alotaibi (Journal of Functional Biomaterials)
The aim of the study is to assess the impact of mechanical surface treatments on the shear bond strength (SBS) of orthodontic brackets bonded to three-dimensional (3D) printed and milled CAD/CAM provisional materials. Sixty cylindrical samples were fabricated for each provisional material. Samples were treated with one of the following surface treatments: aluminum oxide airborne particle abrasion, diamond bur rotary instrument roughening, and phosphoric acid etching (control). Stainless steel brackets were bonded to the samples, and then SBS was tested using a universal testing machine. SEM and digital microscopy were utilized to examine the bonding interface and the failure modes. Two-way ANOVA, one-way ANOVA, Tukey’s HSD, and independent sample t-tests were used for statistical analysis. Results revealed significant differences in SBS between 3D printed and milled samples and significant differences in SBS among most surface treatments, with rotary instrument roughening resulting in the highest values for 3D printed, while airborne particle abrasion leading for milled samples. Digital microscopy indicated that more adhesive remained on 3D-printed samples. SEM analysis revealed varying surface roughness across treatments. Based on the findings of this study, it can be concluded that different surface treatments improve the bonding of orthodontic brackets to provisional crowns.